Improving Teacher Competence in Designing Project-Based Learning Models Through Workshops in The First Semester of the 2018/2019 Academic Year (Madrasah Tsanawiyah Negeri Analysis Study 06 Kerinci) - Refika Mastanora; Oktri Permata Lani; Tistiarni Tistiarni (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
This study aims to describe workshop activities for increasing teacher competence in designing Project Based Learning Models at Madrasah Tsanawiyah Negeri 06 Kerinci. The research was conducted in two cycles and each cycle consisted of four stages, namely: planning, implementing, observing and reflecting. The aspect that is measured in assessing the success of the action is the teacher's readiness to take part in the workshop process and the results of the workshop process. The subject of this research is the teaching staff and the research object is the ability of the teaching staff in designing the Project Based Learning Model. From the results of the analysis, information was obtained that there was an increase in the ability of the Kerinci 06 State Madrasah Tsanawiyah Teachers in designing Project Based Learning Models. This increase was demonstrated by (1) the ability of Kerinci 06 State Madrasah Tsanawiyah Teachers in designing the characteristics of the Project Based Learning Model from 20% in cycle I to 100% in cycle II; (2) the ability of Kerinci 06 State Madrasah Tsanawiyah Teachers in identifying problems with the Project Based Learning Model from 27% in cycle I to 100% in cycle II; (3) the ability of Kerinci 06 State Madrasah Tsanawiyah Teachers in designing the objectives of the Project Based Learning Model, from 27% in cycle I to 100% in cycle II; (4) the ability of Kerinci 06 State Madrasah Tsanawiyah Teachers in preparing the Project Based Learning Model steps, from 20% in cycle I to 100% in cycle II; (5) The ability of Kerinci 06 State Madrasah Tsanawiyah Teachers in designing Project Based Learning Models, from 17% in cycle I to 100% in cycle II.